To convert the equation from vertex form to standard form, we start with the given vertex form equation:
\[ y = -4(x + 5)^2 - 3 \]
-
Expand the squared term: \[ (x + 5)^2 = x^2 + 10x + 25 \]
Now substituting this back into the equation:
\[ y = -4(x^2 + 10x + 25) - 3 \]
-
Distribute the -4: \[ y = -4x^2 - 40x - 100 - 3 \]
-
Combine like terms: \[ y = -4x^2 - 40x - 103 \]
Now, the equation in standard form (Ax^2 + Bx + C) is:
\[ y = -4x^2 - 40x - 103 \]
This is the standard form of the given equation.